ChemInform Abstract: One‐Pot, Facile, Highly Efficient, and Green Synthesis of Acridinedione Derivatives Using Vitamin B1. Issue 17 (April 2016) - Isik, Ahmet; Aday, Burak; Ulus, Ramazan; Kaya, Muharrem
Abstract: Title compounds (IV) are efficiently synthesized through a one‐pot multicomponent condensation in the presence of the easily available, inexpensive, and nontoxic catalyst vitamin B1 .